Beberapa Aspek Psikologi di Dalam Rangkuman Ayat-Ayat Al-Qur'an (Kajian Tafsir Al-Maraghi) - Choliluddin AS (‎‎‎TAZKIYA Journal of Psychology, 2003)
Based on the belief that the Koran is a guide for humans "hundanlinmas" guiding humans on the straight path. Therefore, in the Qur'an there is much that reveals human behavior, both individual (intrapersonal) and social (interpersonal), and at the same time reveals human behavior that is divine (metapersonal).